A Female Case of X-Linked Retinoschisis with Macular Hole Bilaterally - A. Altun (Case Reports in Ophthalmological Medicine)
Purpose. We aimed at reminding that X-linked retinoschisis may also be seen in female patients and share our vitreoretinal surgical experience. Methods. The patient underwent pars plana vitrectomy including the closure of the macular holes with inverted ILM flap technique bilaterally. Lens extractions were performed by phacoemulsification during the removal of silicone oil endotamponade. Patient. An 18-year-old girl with X-linked retinoschisis and large macular holes in both eyes presented to the clinic of ophthalmology. It was confirmed that the patient had RS1 mutation Results. Nine-month-follow-up was uneventful for retinal findings. Significant improvement in visual acuity was achieved, and macular holes were remained closed. Conclusion. In cases with large macular holes due to XLR, an inverted ILM flap technique might be safe and effective. Four-month-silicone-endotamponade might be sufficient.